A comparative study of recycling in the European and Brazilian textile industry - Garvert, Ulrich (2017)
This master thesis analyzes and compares the Brazilian and European textile recycling industries. The research analyzes how both Europe and Brazil can learn from each other to improve the textile recycling process and increase the rate of textile recycling. It puts the topic of textile recycling into a broader perspective of recycling and sustainable supply chains. In that it shows that both in Brazil and Europe there are significant amounts of textile waste both from production processes and from post-consumption. Through the analysis of ten interviews with stakeholders from the European and Brazilian textile recycling industry it is shown that in Europe the industry is significantly ahead through technology and process leadership in certain countries, which is reached through strong research and cooperation along the textile value chain, an aspect not found in Brazil. More specifically it shows that in Brazil a lack of fiscalization of the national policy on solid waste leads to low incentives to comply with the law and to innovate in order to find new solutions for the use of textile waste. As one of the main barriers both in Europe and Brazil the research identifies the lack of sufficient market perspectives and requests consequently investment into research for application of textile waste and its derivative products.